2000
DOI: 10.1136/vr.146.7.179
|View full text |Cite
|
Sign up to set email alerts
|

Production factors that influence the hygienic condition of finished beef cattle

Abstract: A survey was conducted at five UK abattoirs to trace the source of dirty beef cattle and identify factors in the production chain that contributed to their dirtiness. The Meat Hygiene Service Clean Livestock score categories were used and the animals' histories were traced back to their farm of origin. Comprehensive information was collected relating to the farm, transport and lairage phases for 675 cattle from 85 batches. The mean score of the animals on arrival at the abattoir was 1.57, with 2.8 per cent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Slaughtering of visually clean animals is one of the prerequisites to reduce both general abattoir contamination and direct or indirect microbial carcass contamination (Davies et al, 2000); this is also supported by Codex Alimentarius (2005) and EU regulators (EC, 2004a,b). Dirty animals produce carcasses with higher microbial contamination levels compared to control carcasses fabricated from relatively clean animals (Kiermeier et al, 2006;Ridell & Korkeala, 1993).…”
Section: Dirtiness Of Cattle Presented For Slaughtermentioning
confidence: 99%
“…Slaughtering of visually clean animals is one of the prerequisites to reduce both general abattoir contamination and direct or indirect microbial carcass contamination (Davies et al, 2000); this is also supported by Codex Alimentarius (2005) and EU regulators (EC, 2004a,b). Dirty animals produce carcasses with higher microbial contamination levels compared to control carcasses fabricated from relatively clean animals (Kiermeier et al, 2006;Ridell & Korkeala, 1993).…”
Section: Dirtiness Of Cattle Presented For Slaughtermentioning
confidence: 99%
“…These are based on scoring the dirtiness of hides and fleeces and have been developed for research and pre-regulatory evaluation (Collis et al, 2004;Davies, Hadley, Stosic, & Webster, 2000;Hadley et al, 1997;Jordan, McEwen, Wilson, McNab, & Lammerding, 1999;McEvoy et al, 2000) and regulatory use (Ridell & Korkeala, 1993). Jordan et al (1999), in evaluating the reliability of five cattle "faecal dag" rates, demonstrated a high degree of correlation between the rates at both the individual and lot level in lot-fed cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Some published studies indicate that breeds having typically longer hair (e.g. Simmental) have higher potential to become contaminated (Davies, Hadley, Stosic, & Webster, 2000). However, bovines in this study were examined during warmer season (late summer) when hides of both involved breeds had similar hair length.…”
Section: ''Horizontal" Microbial Distribution On Hidesmentioning
confidence: 96%